INTERPRETASI DATA GRAVITASI DAERAH GUNUNG TANGKUBAN PERAHU DAN SEKITARNYA UNTUK MENENTUKAN POTENSI PANAS BUMI - Cahyadi, Richard
Indonesia’s energy usage has been increasing steadily in the past few years. There are a lot of energy sources in Indonesia and one of them is geothermal energy. Geothermal energy became our focus in this experiment, because of ineffective use of geothermal energy as a renewable energy. Geophysics exploration was done, on Tangkuban Perahu Mountain and its surroundings, to find geothermal sources. Gravity method, using Newton gravitation principal, was used for the exploration. Gravity method used gravimeter to measure gravitation around the experiment area. Gravitation data, from measurement, then is corrected to generate complete bouger anomaly. Regional and residual separation is done towards complete bouger anomaly. Then complete bouger anomaly, regional anomaly, and residual anomaly are made into contour map. Contour maps are interpreted so illustrations about underground situations are obtained. Complete bouger anomalies are measured around 270 to 380 mgal. Regional anomalies ranged between 90 to 370 mgal and residual anomalies ranged between -30 to 270 mgal. Three sets of lanes are made to be modeled to show if there’s any geothermal reservoir. line AB has relative density, to the surrounding area, ranges between -0.206 to +0.4524. Relative density in line CD ranged between +0.4901 to -0.155. For line EF, the relative density varied around -0.136 and 0.4160. Modeled results, from gravity method, are then compared to model from Controlled-source Audio-frequency Magnetotellurics (CSAMT) method. The model between two methods are similar.